Application of the Human Well-Being Index to Sensitive Population Divisions: A Children’s Well-Being Index Development - Buck, Kyle D. (Child Indic Res, 2018)
The assessment of community well-being is critical as an end-point measure that will facilitate decision support and assist in the identification of sustainable solutions to address persistent problems. While the overall measure is important, it is equally vital to distinguish variations among groups within the population who may be impacted in a different manner. The U.S. Environmental Protection Agency (US EPA) developed the Human Well-Being Index (HWBI), as a way of measuring these outcomes and assessing community characteristics. The HWBI approach produces a suite of indicators, domains and a final composite index appropriate for characterizing well-being of a population. While generalized approaches are needed, it is important to also recognize variations in well-being across community enclaves. This paper presents an adaption of the HWBI for child populations to test the applicability of the index framework to specific community enclaves. First, an extensive literature review was completed to ensure the theoretical integrity of metric and indicator substitutions from the original HWBI framework. Metric data were then collected, refined, imputed where necessary and evaluated to confirm temporal and spatial availability. A Children’s Well-Being Index (CWBI) value, representing the same indicators and domains of well-being as the original HWBI, was calculated for the population under age 18 across all US counties for 2011. Implications of this research point to an effective, holistic end-point measure that can be tracked over time. Similarly, there is great potential for the application of the original HWBI method to other statistical population segments within the greater US population. These adaptations could help identify and close gaps in equity of resource distribution among these groups.